Effects of Nandrolone Stimulation on Testosterone Biosynthesis in Leydig Cells. Issue 6 (28th December 2015) - Pomara, Cristoforo; Barone, Rosario; Marino Gammazza, Antonella; Sangiorgi, Claudia; Barone, Fulvio; Pitruzzella, Alessandro; Locorotondo, Nicola; Di Gaudio, Francesca; Salerno, Monica; Maglietta, Francesca; Sarni, Antonio Luciano; Di Felice, Valentina; et al.
Abstract : Anabolic androgenic steroids (AAS) are among the drugs most used by athletes for improving physical performance, as well as for aesthetic purposes. A number of papers have showed the side effects of AAS in different organs and tissues. For example, AAS are known to suppress gonadotropin‐releasing hormone, luteinizing hormone, and follicle‐stimulating hormone. This study investigates the effects of nandrolone on testosterone biosynthesis in Leydig cells using various methods, including mass spectrometry, western blotting, confocal microscopy and quantitative real‐time PCR. The results obtained show that testosterone levels increase at a 3.9 μM concentration of nandrolone and return to the basal level a 15.6 μM dose of nandrolone. Nandrolone‐induced testosterone increment was associated with upregulation of the steroidogenic acute regulatory protein (StAR) and downregulation of 17a‐hydroxylase/17, 20 lyase (CYP17A1). Instead, a 15.6 µM dose of nandrolone induced a down‐regulation of CYP17A1. Further in vivo studies based on these data are needed to better understand the relationship between disturbed testosterone homeostasis and reproductive system impairment in male subjects. J. Cell. Physiol. 231: 1385–1391, 2016. © 2015 The Authors. Journal of Cellular Physiology Published by Wiley Periodicals, Inc. Abstract : Anabolic androgenic steroids (AAS) are among the drugs most used by athletes for improving physical performance, as well as for aesthetic purposes. This study investigates the effects of nandrolone on testosterone biosynthesis in Leydig cells using various methods. The results obtained show that testosterone levels increase at a 3.9 µM concentration of nandrolone and return to the basal level a 15.6 µM dose of nandrolone. Nandrolone‐induced testosterone increment was associated with upregulation of StAR and downregulation of CYP17A1.